Teoria neoclássica da lei natural: o bem comum como fundamento prático-razoável da autoridade do direito - Silva, Guilherme Dorneles da (2022)
Analyzing the current legal-political scenario, it is notable that topics such as democracy and human rights are among the most debated by jurists and philosophers. Among the many subjects that involve these themes, there is one that deserves to be highlighted for the way in which it integrates them and harmonizes them in its content. We talk about the concept of common good. Thus, the following work aims to present the common good as the practical-reasonable foundation of the authority of Law in the light of the neoclassical theory of natural law. To this end, with the Australian legal philosopher John Mitchell Finnis as the main author of this current, this will serve as the basis for the elaboration of the research, however the work is not limited to being a defense of his theory, presenting points of disagreement with the author on the interpretation of the application of natural law. It will also make use of the works of names such as Aristotle, Saint Thomas Aquinas, Germain Griesez, among others who in some way contributed to the improvement of jusnaturalist thought. This study is divided into three axes that give rise to the chapters. Firstly, the methodology used by Finnis of the central case and focal meaning is explored, followed by the analysis of the four orders of reality, for the construction of a normative-descriptive theory, which analyzes the Law from the point of view of those who both affect it and are affected by it. In the second moment, there is the foundation of the assumptions of natural law, such as its principles and requirements. And, finally, using the ideas previously raised, the concepts of authority of Law, democracy and human rights are addressed, related to a practical-reasonable proposal for the common good that can fill the conceptual void of this objective, left by the legal system. Brazilian legal system. Therefore, based on the knowledge raised here, the common good being an essential requirement for human beings in the search for basic goods and to consequently achieve their flourishing, it can be understood as the moral foundation of the authority of law.